2019
DOI: 10.3389/fmicb.2019.00737
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Antifungal Susceptibility of Clinical Fusarium Species From Brazil

Abstract: Fusarium is widely distributed in the environment and is involved with plant and animal diseases. In humans, several species and species complexes (SC) are related to fusariosis, i.e., F. solani SC, F. oxysporum SC, F. fujikuroi SC, F. dimerum, F. chlamydosporum, F. incarnatum-equiseti , and F. sporotrichoides . We aimed to investigate the susceptibility of Fusarium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
59
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 76 publications
9
59
1
4
Order By: Relevance
“…AMB and VRC MICs are values for 100% growth inhibition and the listed ITC and POS MICs are the values for 80% growth inhibition.Thirteen of the 25 FSSC isolates were classified as N. keratoplastica (FSSC 2), five as N. falciformis (FSSC 3+4), six as N. suttoniana (FSSC 20), and one as N. petroliphila (FSSC 1) (Table 1). As expected(Espinel-Ingroff et al, 2016;Herkert et al, 2019), all 25 FSSC isolates had very high (>32 mg/l) MICs for the long-tailed azoles, ITC, and POS. Initially, the susceptibility of 15 clinical FSSC isolates to ITC was measured and all isolates showed very high MIC ITC s (>32 mg/l), and so we predicted the same or higher MIC ITC s in FSSC environmental isolates.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…AMB and VRC MICs are values for 100% growth inhibition and the listed ITC and POS MICs are the values for 80% growth inhibition.Thirteen of the 25 FSSC isolates were classified as N. keratoplastica (FSSC 2), five as N. falciformis (FSSC 3+4), six as N. suttoniana (FSSC 20), and one as N. petroliphila (FSSC 1) (Table 1). As expected(Espinel-Ingroff et al, 2016;Herkert et al, 2019), all 25 FSSC isolates had very high (>32 mg/l) MICs for the long-tailed azoles, ITC, and POS. Initially, the susceptibility of 15 clinical FSSC isolates to ITC was measured and all isolates showed very high MIC ITC s (>32 mg/l), and so we predicted the same or higher MIC ITC s in FSSC environmental isolates.…”
supporting
confidence: 75%
“…Most Fusarium species have low susceptibilities to the majority of azole antifungals (Tupaki-Sreepurna et al, 2017;Rotjanapan et al, 2018;Herkert et al, 2019) and patients with IFs have high mortality rates (Esnakula et al, 2013;Silva et al, 2013;Okada et al, 2018). Voriconazole (VRC) and amphotericin B (AMB) are the recommended treatment options for localised infections and IFs (Efeİris et al, 2016;Okada et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Herkert et al reported that the use of sequencing translation elongation factor 1-alpha gene showed a good ability to distinguish and differentiate clinical Fusarium species. 206 Therefore, since Fusarium species cause disseminated infections in patients with hematologic malignancies and these infections are resistant to antifungal treatments, before starting immunosuppressive drugs, patients should be carefully investigated for the presence of infections that involve skin or nail, and more attention should be paid to the cutaneous lesions to reduce the risk of infections by these microorganisms in patients with blood malignancies. Of note, more clinical studies are needed to evaluate the precise function of antifungal agents to inhibit Fusarium species, because proper prophylaxis and treatment of patients with hematologic malignancies may prevent disseminated fusariosis with high mortality in these patients.…”
Section: Fusariosismentioning
confidence: 99%
“…Our results also confirm previous studies regarding the poor in vitro efficacy of ISA against Fusarium spp. (14,15,23,24). Indeed, using the EUCAST reference method, the MIC 50 of our panel of strains was Ͼ16 mg/ml.…”
mentioning
confidence: 87%
“…Isavuconazole (ISA), the last azole derivative marketed, has a more suitable safety profile than voriconazole and is now recommended at grade AI as first-line therapy for invasive aspergillosis by the European Conference on Infections in Leukemia (13). However, data on in vitro efficacy of ISA against Fusarium remain limited (14,15). Most of the previous studies used the Clinical and Laboratory Standards Institute (CLSI) reference method and included a limited number of strains, strains representing a limited number of species, or strains only identified at the species complex level.…”
mentioning
confidence: 99%